Technische Bildung im Sachunterricht der Grundschule am Beispiel von Lernrobotern - Entwicklung und Evaluation eines Fortbildungskonzepts. Posterbeitrag im Rahmen der 31. Jahrestagung der DGfE-Kommission Grundschulforschung und Pädagogik der Primarstufe vom 27. bis 29.09.2023 an der Universität Siegen - Janicki, Nicole

Technische Bildung im Sachunterricht der Grundschule am Beispiel von Lernrobotern - Entwicklung und Evaluation eines Fortbildungskonzepts. Posterbeitrag im Rahmen der gemeinsamen Jahrestagung der DGTB und GATWU vom 21. bis 22.09.2023 an der Universität Potsdam - Janicki, Nicole

Standardization as a Catalyst for Extending Ressouces and Capabilities in Service Systems Engineering: Findings from the omlox case - Marx, Emanuel; Daudrich, Roman; Pauli, Tobias; Matzner, Martin; Beverungen, Daniel (Journal of Service Management Research)
(Smart) service systems have inspired the emergence of a new research area that builds on smart, connected products and networked business models with smart services and brings together various social-science and technological disciplines. However, the factors that lead to successful service systems engineering initiatives have remained under-explored, despite their increasing significance in industry. In particular, the role of standardization is unclear, even though it seems to be central to making smart products interoperable and to establishing innovative (smart) service systems. In an exploratory case study of the standardization initiative omlox, we set out to identify and investigate empirically the effects that standardization can have on engineering (smart) service systems. Our focus is to determine how standardization can assist a company in accessing external resources and capabilities for recombinant service innovation. The results reveal that compliance with a standard enables companies to tap into compatible solutions, data, and knowledge from external stakeholders and that participation in standardization initiatives can be a platform for identifying potential collaboration partners. We conclude that standardization plays a major role in all phases of service systems engineering, from analysis to design and implementation.

Modular Toolbox for Low-Code Development of Individual Augmented Reality Applications in Unity - Eckertz, Daniel; Anacker, Harald; Dumitrescu, Roman (Open Science in Engineering)

Future-robust evolution of product portfolios: Need for action from theory and practice - Schlegel, Michael; Wiederkehr, Ingrid; Rapp, Simon; Koldewey, Christian; Albers, Albert; Dumitrescu, Roman (Procedia CIRP)

Interacting Forces for a Resilient, Future-robust Evolution of Product Portfolios - Wiederkehr, Ingrid; Schlegel, Michael; Koldewey, Christian; Rapp, Simon; Dumitrescu, Roman; Albers, Albert (Procedia CIRP)

Guidelines for providing digital twins - Göllner, Denis; Dzienus, Sophie; Rasor, Rik; Anacker, Harald; Dumitrescu, Roman (Procedia CIRP)

Mehr Innovationen durch Venture Clienting – Fallstudie zur Initiative „Stratosfare“ - Machon, Fabian; Haarmann, Lennard; Rabe, Martin; Dumitrescu, Roman; Bierbüsse, Marie; Tack, Mareen; Hanke, Rebecca; Kinder, Daniel (Vorausschau und Technologieplanung)

Bridging the Gap between Product Innovation and Product Planning: A literature-based Conceptual Investigation - Wiederkehr, Ingrid; Koldewey, Christian; Dumitrescu, Roman; Schlegel, Michael; Albers, Albert

Work in Progress: Development of a Virtual and Interactive Microgrids Learning Environment for Microgrids Sustainability – The case of East Africa - Bogere, Paul; Bode, Henrik; Temmen, Katrin (Learning in the Age of Digital and Green Transition. ICL 2022. Lecture Notes in Networks and Systems)
Partial coverage of the traditional grid is one of the factors that con-tribute to the low electrical energy access levels in developing countries. This often results in long distances between the grid and unconnected communities. Microgrids, due to their distributed energy resources, have the potential to increase energy access levels. However, there is limited access to microgrids-related knowledge. The knowledge is essential for the effective and efficient use of energy, operation, and hence sustainability of microgrids. To contribute to the sustainability of microgrids, a Virtual and Interactive Microgrids Learning Environment (VIMLE) for microgrids knowledge transfer is developed. VIMLE development is guided by design-based research. With knowledge transfer and skills acquisition through the use of VIMLE, local capacity for designing, installing, operating and maintenance of microgrids is built. Skilled local capacity will contribute to microgrids sustainability. Hence, improve electrical energy access levels and contribute to the achievement of SDG 7.
Keywords: Knowledge Transfer; Microgrids; Sustainability

Ontology for Future-robust Product Portfolio Evolution: A Basis for the Development of Models and Methods - Schlegel, Michael; Wiederkehr, Ingrid; Rapp, Simon; Koldewey, Christian; Albers, Albert; Dumitrescu, Roman (Procedia CIRP)

Knowledge Transfer Concepts for Microgrids Sustainability - The Case of East Africa - Bogere, Paul; Temmen, Katrin; Bode, Henrik (2023 IEEE Global Engineering Education Conference (EDUCON))

Towards a systematic approach for Prescriptive Analytics use cases in smart factories - Weller, Julian; Nico Migenda, Nico Migenda; Rui Liu, Rui Liu; Arthur Wegel, Arthur Wegel; Martin Kohlhase, Martin Kohlhase; Wolfram Schenck, Wolfram Schenck; Sebastian von Enzberg, Sebastian von Enzberg; Dumitrescu, Roman

Skill Sets for Microgrids Sustainability - The Case of East Africa - Bogere, Paul; Bode, Henrik; Temmen, Katrin (2023 IEEE AFRICON)

Should I Really do That? Using Quantile Regression to Examine the Impact of Sanctions on Information Security Policy Compliance Behavior - Hengstler, S.; Kuehnel, S.; Masuch, K.; Nastjuk, I.; Trang, Simon Thanh-Nam (Computers & Security)

A Topic Model for the Data Web - Röder, Michael; Kuchelev, Denis; Ngonga Ngomo, Axel-Cyrille (Knowledge Graphs and Semantic Web)
Keywords: sail dice roeder kuchelev ngonga

Explainable Integration of Knowledge Graphs Using Large Language Models - Ahmed, Abdullah Fathi Ahmed; Firmansyah, Asep Fajar; Sherif, Mohamed; Moussallem, Diego; Ngonga Ngomo, Axel-Cyrille (Natural Language Processing and Information Systems)
Linked knowledge graphs build the backbone of many data-driven applications such as search engines, conversational agents and e-commerce solutions. Declarative link discovery frameworks use complex link specifications to express the conditions under which a link between two resources can be deemed to exist. However, understanding such complex link specifications is a challenging task for non-expert users of link discovery frameworks. In this paper, we address this drawback by devising NMV-LS, a language model-based verbalization approach for translating complex link specifications into natural language. NMV-LS relies on the results of rule-based link specification verbalization to apply continuous training on T5, a large language model based on the Transformerarchitecture. We evaluated NMV-LS on English and German datasets using well-known machine translation metrics such as BLUE, METEOR, ChrF++ and TER. Our results suggest that our approach achieves a verbalization performance close to that of humans and outperforms state of the art approaches. Our source code and datasets are publicly available at https://github.com/dice-group/NMV-LS.

Unsupervised Relation Extraction with Sentence level Distributional Semantics - Manzoor, Ali; Saleem, Muhammad; Ngonga Ngomo, Axel-Cyrille (2023 IEEE 17th International Conference on Semantic Computing (ICSC))

Automating the Discovery of Linking Candidates - Röder, Michael
Keywords: dice roeder

Neural Class Expression Synthesis (Extended Abstract) - KOUAGOU, N'Dah Jean; Heindorf, Stefan; Demir, Caglar; Ngonga Ngomo, Axel-Cyrille (NeSy 2023, 17th International Workshop on Neural-Symbolic Learning and Reasoning, Certosa di Pontignano, Siena, Italy)
Keywords: 318 SFB-TRR demir dice enexa heindorf knowgraphs kouagou ngonga sail